The "Game of Implants": A Perspective on the Crisis-Prone History of Breast Implants. (31st January 2019) - Deva, Anand K; Cuss, Amanda; Magnusson, Mark; Cooter, Rodney
Abstract: Since their introduction into the market, breast implants have been the subject of many controversies. It is timely to examine the forces that have shaped the breast implant industry to make it what it is today. This review will concentrate more on the use of implants in aesthetic surgery rather than their use in breast reconstruction, but some of the factors have relevance to both indications.